Ultrasonic diagnostics of concrete destruction under the influence of corrosion environment - N. M. Tolypina; D. Yu. Danilov (Вестник СибАДИ)
Introduction. Modern methods of studying the corrosion damage of concrete are quite lengthy and time-consuming, which makes their use difficult. This necessitates the search for new approaches to study the destruction of concrete under the influence of aggressive media. Currently, the ultrasound diagnostic method is effectively used to identify various structural defects, but the possibility of its use for concrete corrosion studies is poorly understood. This work is devoted to filling this gap.The methods of research. Concrete samples of 2.5x2.5x10 cm and 2.5x2.5x16 cm of various composition (cement: placeholder = 1:9, 1:7, 1:5). The control samples hardened under normal conditions, the test samples were stored in various aggressive environments. The samples of all storage media were subjected to periodic tests on the Pulsar-2.2 ultrasound diagnostic device. In parallel, the strength parameters obtained by the destructive method on the PGM-100MG4 hydraulic press, as well as the resistance coefficient, were determined.Results. The relationship between the growth periods, extremes and abrupt changes in the velocity of passage of ultrasonic waves and the stages of strength gain, the conditions of hardening of samples, and time factors has been established. It is shown that ultrasound diagnostics is quite sensitive to the processes caused by the corrosion destruction of concrete and allows us to obtain reliable data, while the strength and coefficient of resistance do not always adequately reflect the development of corrosion processes. It has been established that the use of ultrasound diagnostics makes it possible to increase the reliability of the results of concrete corrosion studies.Conclusion. The use of the ultrasound diagnostic method enables to obtain new data on the processes of concrete destruction under the influence of aggressive media, which makes it possible to increase the reliability of the results of concrete corrosion studies.